The Influence of Microbial Consortium in Bioremediation Process using Bioreactor - Nur Hidayatul Alami (IPTEK Journal of Science, 2014)
bioreactor is one of ex situ bioremediation technologies that can be applied to solve the problem of oil contaminated soil. Bioremediation process can be enhanced by using microbial consortium that has specific characteristics to degrade the contaminant. The aim of this research was to know the effect of various concentrations of microbial consortium and incubation time on bioremediation of crude oil contaminated soil by using a bioreactor. The influence of microbial consortium concentration and incubation time in bioremediation can be known from increasing of total heterotrophic microbial and decreasing of oil residue (g / g-soil). The type of the research was experimental with 1 control (without microbial consortium adding) and 3 treatments, including microbial consortium concentration of 2.5% (K1), 5% (K2), and 7.5% (K3). The incubation times were 0-4 weeks. The resulted data of crude oil residue (g / g-soil) were analyzed descriptively and statistically by one-way analysis of variances (one-way ANOVA) and Duncan test (p = 0.05). The results of this research indicate concentrations of microbial consortium and incubation time affect bioremediation process in a bioreactor. K1 (2.5%) was known to be the most effective to decrease oil residue up to 7%, if compared with the control at 2 weeks of incubation time.